2002
DOI: 10.1002/lsm.10096
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimentally induced transient cerebral ischemia with low energy laser inhibits nitric oxide synthase activity and up‐regulates the expression of transforming growth factor‐beta 1

Abstract: Low energy laser could suppress the activity of NOS and up-regulate the expression of TGF-beta1 after stroke in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 55 publications
1
74
1
3
Order By: Relevance
“…7,8,15 Lapchak et al, 16 Oron et al, 17 and DeTaboada et al 18 have shown in 2 different animal models a positive impact of infrared laser therapy on the experimental, ischemic stroke treatment outcomes in New Zealand rabbits (rabbit small clot embolic stroke model [RSCEM]) and Sprague-Dawley rats (permanent middle cerebral artery occlusion). Lapchak has shown that laser treatment at 6 hours poststroke onset in RSCEM improved behavioral performance and produced a durable effect that was measurable 21 days after embolization.…”
mentioning
confidence: 99%
“…7,8,15 Lapchak et al, 16 Oron et al, 17 and DeTaboada et al 18 have shown in 2 different animal models a positive impact of infrared laser therapy on the experimental, ischemic stroke treatment outcomes in New Zealand rabbits (rabbit small clot embolic stroke model [RSCEM]) and Sprague-Dawley rats (permanent middle cerebral artery occlusion). Lapchak has shown that laser treatment at 6 hours poststroke onset in RSCEM improved behavioral performance and produced a durable effect that was measurable 21 days after embolization.…”
mentioning
confidence: 99%
“…Quando ocorre uma lesão tecidual, o processo de reparo é modulado pela atividade celular das células da resposta inflamatória e das células da borda da lesão e por uma rede de citocinas e de fatores de crescimento que influenciam a migração, a proliferação e a diferenciação celular para o local da lesão tecidual 26,27 . O TGF-β2 é uma citocina pró-inflamatória envolvida em processos fisiológicos e patológicos, incluindo remodelamento vascular (angiogênese e neogênese) e fibrose cutânea 26,[28][29][30] .…”
Section: Discussionunclassified
“…Os resultados sugeriram que a LLLT é um método útil e não invasivo para regular a intensidade da reação inflamatória, sendo instrumento importante na cicatrização de feridas cutâneas 6 . Estudo envolvendo tratamento com LLLT na isquemia cerebral induzida experimentalmente sugere que este tipo de terapia pode inibir a produção do NO e regular a expressão da citocina TGF-β2 que apresenta potencial anti--inflamatório além de induzir a proliferação fibroblástica, controlando o processo cicatricial 27 . Diversos pesquisadores também têm estudado o papel imunomodulador pró-inflamatório do NO através da elevação dos níveis de COX2 [14][15][16][17] .…”
Section: Discussionunclassified
“…Although the specific mechanism remains unknown, laser-induced intracellular generation of reactive oxygen species probably involves energy transfer from PPIX and other photoacceptors present in the cell. In addition, several groups have described cellular functions mediated by nitric oxide (NO), which is upregulated by laser irradiation, as well as by inducible nitric oxide synthase (iNOS) [79,[81][82][83][84]. The mechanism of laser-induced control of cellular functions is believed to hinge on the regulation of photoacceptor activity and the intracellular levels of reactive oxygen species.…”
Section: Redox Pathwaysmentioning
confidence: 99%